The Strangeness of Abū Tammām’s Poetry from the Perspective of Classical Criticism - bennabet, samir; zerdoumi, ismail (El Omda in Linguistics and Discourse Analysis, 2023)
This study came to shed light on the phenomenon of ambiguity - as a literary problem - that was associated in the Abbasid era with Abu Tammam, due to his employment of strange pronunciation and meaning to the point of incomprehensible, which sparked a wide critical movement around his poetry. In order to overcome this problem, Abu Tammam focuses on the need for its recipients to have a broad culture in order to understand his poetry and realize its meanings that seem strange. Critics have attributed Abu Tammam’s tendency to the stranger to cultural factors based on the poet’s permanent connection to ancient poetry and the abundance of his preserved from it, and his desire to alienate and imitate those of the early poets who passed away, which means that strange of Abu Tammam is not a linguistic phenomenon as much as it is an artistic phenomenon.